Characterization and comparison of sodium-glucose cotransporter 2 inhibitors in pharmacokinetics, pharmacodynamics, and pharmacologic effects - Atsuo Tahara; Toshiyuki Takasu; Masanori Yokono; Masakazu Imamura; Eiji Kurosaki (Elsevier, 2016)
The sodium-glucose cotransporter (SGLT) 2 offer a novel approach to treating type 2 diabetes by reducing hyperglycaemia via increased urinary glucose excretion. In the present study, the pharmacokinetic, pharmacodynamic, and pharmacologic properties of all six SGLT2 inhibitors commercially available in Japan were investigated and compared. Based on findings in normal and diabetic mice, the six drugs were classified into two categories, long-acting: ipragliflozin and dapagliflozin, and intermediate-acting: tofogliflozin, canagliflozin, empagliflozin, and luseogliflozin. Long-acting SGLT2 inhibitors exerted an antihyperglycemic effect with lower variability of blood glucose level via a long-lasting increase in urinary glucose excretion. In addition, ipragliflozin and luseogliflozin exhibited superiority over the others with respect to fast onset of pharmacological effect. Duration and onset of the pharmacologic effects seemed to be closely correlated with the pharmacokinetic properties of each SGLT2 inhibitor, particularly with respect to high distribution and long retention in the target organ, the kidney. While all six SGLT2 inhibitors were significantly effective in increasing urinary glucose excretion and reducing hyperglycemia, our findings suggest that variation in the quality of daily blood glucose control associated with duration and onset of pharmacologic effects of each SGLT2 inhibitor might cause slight differences in rates of improvement in type 2 diabetes.